2022
DOI: 10.1186/s12951-022-01720-2
|View full text |Cite
|
Sign up to set email alerts
|

Pro-efferocytic macrophage membrane biomimetic nanoparticles for the synergistic treatment of atherosclerosis via competition effect

Abstract: Macrophages participate in many links in the pathological process of atherosclerosis (AS) and the regulation of influence of macrophages at the molecular level might be a new avenue for AS treatment. For this aim, the macrophage membrane biomimetic nanoparticles, derived from macrophage membrane coated SHP1i-loaded liposome NPs (MM@Lips-SHP1i) was designed. Due to the reservation of intrinsic membrane proteins and function from macrophages, the biomimic nanoparticles could effectively evade clearance by the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…However, the plaque area was differentially reduced in the ApoE −/− mice with treatments, compared with the Model group. Compared with the free Evol group (~ 13.33%) and Lipo@E NPs group (~ 12.44%), (Lipo + M)@E NPs showed the strongest inhibitory effect on aortic plaque formation with plaque area of ~ 3.78% (Fig.7B&C), which was consistent with previous reports [ 38 ]. This result demonstrated that this biomimetic nanoparticle could actively target, accumulate and penetrate into plaque.…”
Section: Resultssupporting
confidence: 91%
“…However, the plaque area was differentially reduced in the ApoE −/− mice with treatments, compared with the Model group. Compared with the free Evol group (~ 13.33%) and Lipo@E NPs group (~ 12.44%), (Lipo + M)@E NPs showed the strongest inhibitory effect on aortic plaque formation with plaque area of ~ 3.78% (Fig.7B&C), which was consistent with previous reports [ 38 ]. This result demonstrated that this biomimetic nanoparticle could actively target, accumulate and penetrate into plaque.…”
Section: Resultssupporting
confidence: 91%
“…Macrophage membrane was obtained according to the previously reported method [ 34 ] [ 35 ]. The obtained macrophage membrane was repeatedly extruded 10 times in PBS buffer through the polycarbonate porous membrane of 800 and 400 nm with an Avestin Mini-extruder, and the obtained vesicles of macrophage membrane were stored at 4 ℃.…”
Section: Methodsmentioning
confidence: 99%
“…MM@Lips-SHP1i NPs would battle macrophages in the plaque site in vivo to interact with oxidized low-density lipoprotein and LPS, decrease the intake of fresh lipids by macrophages, and decrease the production of foam cells. 487 …”
Section: Nanotechnology In Non-infectious Inflammatory Diseasesmentioning
confidence: 99%